PERAN DINAS LINGKUNGAN DALAM PENGENDALIAN PENCEMARAN AKIBAT TUMPAHAN MINYAK OLEH PERTAMINA DI KOTA PAREPARE - Asram A.T. Jadda, Sadriyah Mansur, Hartono Hamzah, Kaswin (FAKULTAS HUKUM UM PAREPARE, 2022)
This study aims to determine the role of the Department of the Environment in controlling marine pollution due to the Pertamina oil spill in Parepare City. This study uses a descriptive-qualitative type of research with an empirical normative approach. The data collection techniques used are by means of literature studies, field studies and interviews. Based on this research, it shows that in carrying out its role the Parepare City Environmental Service makes several efforts including reporting cases and field facts, supervision and monitoring, status checks in pollution control, water quality testing, prevention and recovery, as for the obstacles the Parepare City Environmental Service has. In controlling marine pollution in Parepare City there are two (2) factors, namely, internal and external factors